2010
DOI: 10.1177/001979391006300409
|View full text |Cite
|
Sign up to set email alerts
|

Enforcement and Compliance with Labor Regulations in Argentina

Abstract: The author analyzes the effect of government enforcement on compliance with labor regulations in Argentina, a country where only half of the workforce receives all the benefits to which they are legally entitled. Constructing panel data for the period 1995?2002 across provinces and using the number of labor inspectors per capita as a proxy for enforcement, he estimates the panel data set spanning the time period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
0
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 13 publications
2
107
0
13
Order By: Relevance
“…Alm et al 1992, Andreoni et al, 1998. Several more recent non-experimental studies in developing countries have found evidence that the degree of enforcement matters for labor informality (Ronconi, 2007;Almeida and Carneiro, 2012), but there is no reliable evidence we are aware of on the impacts of enforcement on firm informality.…”
Section: Introductionmentioning
confidence: 90%
“…Alm et al 1992, Andreoni et al, 1998. Several more recent non-experimental studies in developing countries have found evidence that the degree of enforcement matters for labor informality (Ronconi, 2007;Almeida and Carneiro, 2012), but there is no reliable evidence we are aware of on the impacts of enforcement on firm informality.…”
Section: Introductionmentioning
confidence: 90%
“…I expect the usual forces analyzed by other papers to be at play here -the deterrence effect of labor inspections and the movement of workers to the informal sector of the economy where firms are not inspected (Ronconi, 2010;Bhorat et al 2012;Almeida and Carneiro, 2012;. However, the design of labor market regulations in Peru jointly to a scheme of penalties for violations to the labor rules that depends on the size of the firms add a margin of adjustment not analyzed before.…”
Section: Introductionmentioning
confidence: 90%
“…These regional variables are included to control for characteristics that can be correlated with the level of enforcement and can affect the level of compliance as well, like the regional business and political cycle and the development level (Piore and Schrank, 2008;Ronconi, 2010;Murillo et al, 2011;Ronconi, 2012). These variables are the fiscal result as a percentage of total incomes, the logarithm of the amount of per capita money lent by the banking system to the private sector, the logarithm of the per capita MWh of electricity consumed, the regional unemployment rate, the logarithm of the average per capita household income, the share of poor households receiving food programs, the Gini coefficient of the per capita household income, and the share of precarious dwellings.…”
Section: Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies attempt to measure the extent and depth of noncompliance with a number of legally mandated requirements such as minimum wages, maximum working hours, occupational health and safety, and social security coverage. Research shows that noncompliance with labor regulations is pervasive, particularly in less developed countries (Bhorat et al, 2012;Kanbur et al, 2013;Rani et al 2013;Ronconi, 2010). 2 There is, however, debate about the welfare implications of this fact.…”
Section: Introductionmentioning
confidence: 99%